Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The role of transformational leadership in enhancing organizational reputationA field study on administrative staff in health affairs in JeddahMr. Mohammed Khalid Mohammed Alsulami, Co-Prof. Faisal Ahmed Abed Shuaibi2. Advertising policies and their role in increasing the market share: An applied study on Saleh Hussain Al Salama Group of Companies, Kingdom of Saudi ArabiaMr. Bandar Abdulraheem Alghamdi3. The role of the private sector in the development of the economics and services of Hajj and UmrahMr. Ibrahim Ahamad Hurubi4. The impact of internal audit quality on fighting corruption in the Qatari public sectorDr. Omer Mahgoub El-Hussaein5. The Reality of Managing Academic Competencies at Prince Sittam Bin Abdulaziz UniversityMrs. Hessah Mohammed Alkhonain, Dr. Nora Hamad Almashal6. Functional combination and its impact on employee productivityDr. Rayan Adnan Aziz Alrahman7. The role of lean management in achieving institutional excellenceAn Empirical Study: Asir Central Hospital in AbhaMs. Neamah Adel AlDoshan
Keywords: Journal of Economic, Administrative and Legal Sciences